2010
DOI: 10.1590/s0066-782x2010005000135
|View full text |Cite
|
Sign up to set email alerts
|

Redução da pressão arterial, da IMC e da glicose após treinamento aeróbico em idosas com diabete tipo 2

Abstract: Background: The aging process is associated with the development of several diseases, which can be attenuated by the practice of physical activities. Aerobic training is an effective method to maintain and improve cardiovascular function. Additionally, it has a crucial role in the prevention and treatment of several chronic-degenerative diseases, especially diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
21

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 28 publications
1
10
0
21
Order By: Relevance
“…The sociodemographic characteristics of individuals participating in the study are similar to other studies of individuals with DM, as age over 60 years; (21,22) most female, (22) with a partner (23) , low level of education, (22) retired (23) and an income above the minimum salary. (22) In the second phase of the study, there was an increase of postprandial blood glucose and blood pressure in the control group and showed statistically significant reduction in HbA1c in both groups, as well as fasting glucose and DBP in EG.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The sociodemographic characteristics of individuals participating in the study are similar to other studies of individuals with DM, as age over 60 years; (21,22) most female, (22) with a partner (23) , low level of education, (22) retired (23) and an income above the minimum salary. (22) In the second phase of the study, there was an increase of postprandial blood glucose and blood pressure in the control group and showed statistically significant reduction in HbA1c in both groups, as well as fasting glucose and DBP in EG.…”
Section: Discussionsupporting
confidence: 52%
“…Individuals who participated in health education programs showed reduced levels of HbA1c, fasting glucose levels for a few months (23) and blood pressure. (21) Health education can contribute to the reduction of glycemic indexes in individuals presenting values above normal. (9,10) However, even without the reduction of the values, it is emphasized that health education should be considered, due to their cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…They identified an association between excess weight with high blood pressure levels, which emphasizes the need for intervention and for nutritional status control measures, such as dietary education programs aimed at the prevention and treatment of obesity as a risk factor for cardiovascular diseases in the pediatric and older age ranges. Monteiro et al40 analyzed the effect of a 13-week aerobic training program on blood pressure, body mass index and glycemic levels in elderly women with type-2 diabetes mellitus and found that the program was enough to promote significant decrease in the diastolic blood pressure and glycemic levels.…”
Section: Introductionmentioning
confidence: 99%
“…21 Em indivíduos portadores de diabetes mellitus, uma alimentação balanceada associada a um programa de exercícios físicos regulares vem mostrando benefícios na melhoria do controle glicêmico, na redução da frequência cardíaca, da pressão arterial, dos níveis de lipídios plasmáticos, de variáveis antropométricas e do índice de massa corporal (IMC). 34,35 No presente estudo, algumas limitações podem ser apontadas em relação à cautela na interpretação dos dados apresentados, pois a prevalência do diabetes mellitus referido indica uma estimativa dos casos conhecidos. Além disso, o desenho transversal do estudo não permite distinguir se os fatores que apresentaram associação com o diabetes mellitus referido são causas ou efeitos da própria doença.…”
Section: Discussionunclassified